Preliminary Study on Wound Healing Activity of Propolis in Albino Rats - ATAYOGLU, A.Timucin; SILICI, Sibel (International Journal of Innovative Research in Medical Science, 2016)
Background: Infection can lead to delayed wound healing. Recently it has been shown that propolis which is used in complementary medicine has an antibacterial and anti-inflammatory effect. The aim of this study is to determine whether propolis may contribute to wound healing. Material and Methods: Twenty-one male Wistar albino rats were randomly divided into three groups. Group1 and Group 2 were topically treated with propolis ointment and Thiocillin® oinment, respectively while Group 3 was the control group. On incision wound model, Thiocillin® and propolis ointments were applied on wound sites once daily for 30 days and the mean epidermal thickness (MET) at the 30th day was compared while antimicrobial activity of propolis was studied against different pathogens as well. Results: Propolis exhibited in vitro antibacterial activity against Staphylococcus aureus, Escherichia coli, Streptococcus sp. and Pseudomonas sp. It is observed that the MET in the groups of Propolis ointment and Thiocillin® ointment were significantly greater than that of the control group, while the MET in the group of propolis ointment was significantly greater than that of Thiocillin® ointment treated group. Conclusion: Propolis is effective in wound healing. Further study in-depth is necessary to probe into clinical correlation.